Analisis Syar’iyyah Ijtihad Umar Bin Khattab terhadap Hadd Sariqah - Hisan, Khairatun; Santoso , Arif Dian (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
Umar bin Khattab acknowledged as a reformer in Islamic Criminal Law. He considered as a source of authority for liberal Muslim thinkers over his thoughts. His ideal of ijtihad differ from what being understood in the Qur'an and Sunnah which raises the pros and cons among the companions. Even liberal thinkers consider Caliph Umar bin Khattab has a hermeneutic consciousness and an actual rationalist figure. One example of his ijtihad is declining the implementation of hadd punishment of cutting off hands for thieves under certain circumstances. The research aims to re-examine of Umar bin Khattab ijtihad, especially on hadd of sariqah. This research is a qualitative literature review, where data come from the Quran, Hadith, and references which further analyzes by descriptive-analytical methods. The result of the study showed that inapplicability of sariqah punishment due to the emergencies, namely famine. Also, there was doubt in the crime that caused Umar to abhor the punishment. Based on these reasons, then Umar's ijtihad is allowed according to the Shari'ah and not a form of Shari'ah deconstruction.